2018
DOI: 10.1016/j.anr.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Contributions and Limitations of National Cervical Cancer Screening Program in Korea: A Retrospective Observational Study

Abstract: The Korean national cervical cancer screening program has improved in accuracy and has contributed to detection of early stage of cervical cancer over the years. Along with efforts to promote participation in cancer screening programs, quality control over the screening program should be enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Contrary to this study, the incidence of cervical cancer has been decreasing in other high‐resource countries 2‐4 . This includes other East Asian countries whose success is considered to be the result of a combination of cervical cancer control measures, particularly organized cervical screening 4,32‐34 . Cervical screening with a highly sensitive and precise test has been proven to reduce the incidence and mortality of cervical cancer by increasing early detection 35‐37 .…”
Section: Discussionmentioning
confidence: 72%
“…Contrary to this study, the incidence of cervical cancer has been decreasing in other high‐resource countries 2‐4 . This includes other East Asian countries whose success is considered to be the result of a combination of cervical cancer control measures, particularly organized cervical screening 4,32‐34 . Cervical screening with a highly sensitive and precise test has been proven to reduce the incidence and mortality of cervical cancer by increasing early detection 35‐37 .…”
Section: Discussionmentioning
confidence: 72%
“…11 , 13 Cervical cancer can be prevented by a combination of organizational screening and human papillomavirus (HPV) vaccination. 7 , 9 , 51 , 52 In Japan, the national HPV vaccination program has been substantially halted by the fear of potential adverse effects. 53 , 54 A simulation modeling study demonstrated that rapid restoration of vaccination coverage and catch-up for missed cohorts could avoid approximately 50,000 cervical cancer cases in 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, even though cervical cancer screening rates were low in 2002 (30.8%), they have increased gradually since then (40.9% in 2012) [ 17 ]: the lifetime screening rate of cervical cancer was much higher (74.8%) [ 18 ]. The sensitivity and specificity of Pap smear tests in 2014 were 91.2% and 97.7%, respectively [ 19 ]. We believe that the quality of the Pap smear test might have contributed to the observed effects in this study.…”
Section: Discussionmentioning
confidence: 99%